2011
DOI: 10.1186/1471-2458-11-284
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a community-based adolescent obesity prevention project in Tonga

Abstract: BackgroundThe rising burden of obesity in Tonga is alarming. The promotion of healthy behaviours and environments requires immediate urgent action and a multi-sectoral approach. A three-year community based study titled the Ma'alahi Youth Project (MYP) conducted in Tonga from 2005-2008 aimed to increase the capacity of the whole community (schools, churches, parents and adolescents) to promote healthy eating and regular physical activity and to reduce the prevalence of overweight and obesity amongst youth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 12 publications
3
62
0
Order By: Relevance
“…In developed countries, irrespective of NFSI, the prevention of obesity in children and adolescents is a priority focus of school health programs, but results in this regard have been mitigated (17). It was suggested that multi-component interventions (promoting healthy eating, less sedentary behavior and more physical activity), particularly when they target whole communities and environments rather than merely schoolchildren and education, may be more effective in developed countries (17), as well as in developing countries such as in the Pacific (18). In a metropolitan area in North India, a case-control study among school adolescents shows for the first time that a low-cost nutrition and lifestyle educational intervention was effective in improving participants' diet, reducing abdominal adiposity and reducing fasting blood glucose levels, after only a few months (19).…”
Section: The Nutrition-friendly Schools Initiative and Its Rationalementioning
confidence: 99%
“…In developed countries, irrespective of NFSI, the prevention of obesity in children and adolescents is a priority focus of school health programs, but results in this regard have been mitigated (17). It was suggested that multi-component interventions (promoting healthy eating, less sedentary behavior and more physical activity), particularly when they target whole communities and environments rather than merely schoolchildren and education, may be more effective in developed countries (17), as well as in developing countries such as in the Pacific (18). In a metropolitan area in North India, a case-control study among school adolescents shows for the first time that a low-cost nutrition and lifestyle educational intervention was effective in improving participants' diet, reducing abdominal adiposity and reducing fasting blood glucose levels, after only a few months (19).…”
Section: The Nutrition-friendly Schools Initiative and Its Rationalementioning
confidence: 99%
“…Ma'alahi Youth Project Fotu et al (26,43,68,69) Healthy breakfast, school lunches, F&V intake, water…”
Section: Fandv Intakementioning
confidence: 99%
“…However, limited large scale studies are beginning to share evaluation tools on websites for public use and descriptions of process evaluation objectives and associated data collections tools employed are increasingly being published in peer reviewed journals. This has occurred in interventions in mental health [45], weight management [16] and physical activity [46]. There are additionally some evaluation guides available online (grey literature) that incorporate evaluation templates as well as sample questions for semi-structured interviews and focus groups [47,48].…”
Section: Data Collection Methods and Toolsmentioning
confidence: 99%
“…Common elements assessed in a process evaluation include program reach, fidelity in relation to program protocol, program context, quality and dose delivered and received by participants [14,15]. A community based obesity prevention study in adolescents living in Tonga completed a process evaluation by research staff recording all intervention-related activities, the frequency of the activity, the reach of that activity (how many people were involved in the program) and the resources required [16]. The purpose of a formative evaluation is to improve the quality of performance or the delivery of the program prior to rollout and is conducted either before or during the program [17].…”
Section: Evaluation Conceptsmentioning
confidence: 99%